DEVELOPMENT OF THE ETINTEC STUDENT BOOK (ETHNOSCIENCE-BASED INTERACTIVE TEACHING STUDENT BOOK) AS AN INTERACTIVE LEARNING MEDIA BASED ON THE TYPICAL PONOROGO CULTURE ON ECOLOGY AND BIODIVERSITY MATERIALS - Munawaroh, Zahrotul; Sari, Putri Kemala; Pambudi, Bagas Setiyo; Ekapti, Rahmi Faradisya (INSECTA: Integrative Science Education and Teaching Activity Journal, 2022)
Science learning is still often considered difficult. But basically, it will feel easy if it is based on interest. Ecology and biodiversity material, which mostly contains theory, requires a strategy to get students interested, namely by associating something around them with that material. Based on this, research was carried out with the aim of developing an interactive student book called the Etintec Student Book on ecology and biodiversity based on the ethnoscience of culture typical of Ponorogo Regency. This research is development research with a modified model from 4D to 3D with stages including defining, designing, and developing. In the define stage, things are found that become a reference for designing innovative products, starting from learning problems to development goals. At the design stage, the Etintec Student Book product was produced including layout design, material preparation (narration, comics, Ponorogo cultural reviews), evaluation preparation consisting of crossword puzzles (TTS), digital evaluation with quizizz (QR Code), and project evaluation. And at the development stage validation was carried out on several learning media experts from science teachers and lecturers with a score of 3.58, meaning that this product can be used with minor improvements. This research can be continued with the field practice test phase and the effectiveness test so that later the Etintec Student Book can be widely used and the dissemination stage can be carried out.